Case report: Spinal drop metastasis of IDH-mutant, 1p/19q-codeleted oligodendroglioma - Karaman, Ahmet Kursat; Korkmazer, Bora; Urganci, Nil; Baş, Gülçin; Arslan, Serdar; Comunoglu, Nil; Hanci, Mehmet Murat; Kızılkılıç, Osman (Frontiers in Neurology, 2022)
Background Symptomatic spinal metastases of oligodendroglioma are rare. Moreover, none of the previously published cases demonstrated the typical IDH mutation and 1p/19q-codeletion for this glial tumor. This case presents an IDH mutant, 1p/19q-codeleted oligodendroglioma with multiple spinal drop metastases. Case description We report a case of a 55-year-old woman with left frontal grade 3 oligodendroglioma diagnosed 3 years ago. No tumor recurrence was observed in post-operative follow-up MRI examinations. However, she was admitted to our institution again with severe low back pain. Gadolinium enhanced MRI of the spine revealed an intradural, extramedullary metastatic lesion between T11–L1 levels and multiple enhancing metastatic tumor deposits around cauda equine roots between L4–S1. T11–T12 midline laminectomy was performed and gross total resection of metastatic lesions was achieved. Final histological diagnosis of the spinal lesions was WHO Grade 3 Oligodendroglioma, IDH-mutant, 1p/19q-codeleted. Conclusion This case is the first molecularly-defined spinal metastatic oligodendroglioma. The possibility of drop metastasis should be kept in mind in oligodendroglioma patients with spinal cord-related symptoms. There is no standard approach for the diagnosis and treatment of spinal metastases of this type of glial tumor.